Exploratory Data Analysis for the Digital Humanities: The Comédie-Française Registers Project Analytics Tool. Issue 5 (4th July 2017) - York, Christopher
ABSTRACT: In 2008 the Comédie-Française, France's pre-eminent dramatic troupe and theatre, embarked on an ambitious project to digitise its remarkable collection of ticket receipts dating from the theatre's opening in 1680 to just after the French Revolution. This paper describes the design and development of a general-purpose online data analytics tool to make meaning from the resulting database: its technical and theoretical underpinnings, its audience and constraints, its user-base and expectations.